2012
DOI: 10.1088/0963-0252/21/2/025006
|View full text |Cite
|
Sign up to set email alerts
|

Electric field distribution in the cathode-fall region of an abnormal glow discharge in hydrogen: experiment and theory

Abstract: We present the results of an experimental and theoretical study of the electric field distribution in the cathode-fall (CF) region of an obstructed abnormal glow discharge in hydrogen. The distribution of electric field strength was measured using an improved Stark polarization spectroscopy technique of the hydrogen Balmer beta line profile. The developed technique extends field measurements to the low-field region while remaining in good agreement at larger field strengths with the well established Stark pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Electric fields of this magnitude can be expected to pro duce high energy electrons. The collisional nature of this dis charge and the high collision cross sections for N 2 vibrational transitions are going to thermalize a low energy component of the electron population leaving one or more groups of non equilibrium and nonlocal high energy electrons [32][33][34][35][36][37].…”
Section: Inside a Plasma Sourcementioning
confidence: 99%
“…Electric fields of this magnitude can be expected to pro duce high energy electrons. The collisional nature of this dis charge and the high collision cross sections for N 2 vibrational transitions are going to thermalize a low energy component of the electron population leaving one or more groups of non equilibrium and nonlocal high energy electrons [32][33][34][35][36][37].…”
Section: Inside a Plasma Sourcementioning
confidence: 99%
“…Under the influence of the magnetic field on T e and N e for the CF region, the plasma is very intense (very thin bright ring) [19] [20], where the radial distributions of the electron density has its highest value at the edge, whereas the magnetic field is maximum, as shown in Figure 8. The electron temperature changes very little.…”
Section: The Radial Distribution Of the Electron Temperature And Densitymentioning
confidence: 99%
“…It is particularly suitable for measurements of the electric eld distribution in the CS using Balmer lines polarized Stark spectroscopy in hydrogen or hydrogen-containing discharges, and employing different Stark components polarized either linearly, parallel to the electric eld F direction (p-polarization), or circularly, in the plane perpendicular to F (s-polarization). Several hydrogen-based studies showed well-dened electric eld distribution in the CS [15][16][17][18][19][20][21][22] and constituted the experimental basis for establishing the iterative kinetic model of the CS. 21,22 Further investigations were extended to the inuence of the Stark effect on the non-hydrogen lines starting with helium, [23][24][25][26] towards heavier elements like neon and argon.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we assumed a simple linear regression electric field distribution model F ( d ) = F max (1 − d / d c )described in standard textbooks, taking into account that typically around 90% of the applied discharge voltage gets consumed in the CS to produce the electric field. Following several reported experimental results, 18–21,23,24,32 which show that the F ( d ) exhibits a plateau at the maximum value F max , stretching from the cathode surface to the distance of about 20% of the total CS length d c , we hereby additionally assumed, for the purpose of simplicity, that the F = F max remains constant within the first 20% of the CS (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%